System analysis of DSTTD-CDMA system with polarization diversity for frequency-selective channel. (January 2018) - Vasanth Raj, P.T.; Vishvaksenan, K.S.
Highlights: We investigate the performance of turbo coded DSTTD-CDMA system for DL transmission. Performance is analyzed using block-Nulling detection algorithm when communicating over LTE-Extended vehicular channel models specifications. AES algorithm provides expected results in data hiding and DWT compression achieves required compression ratio. DSSTD system with dual-Polarized antennas offers higher throughput with less reduced size of Mobile unit. Coded dual-Polarized DSTTD-CDMA system achieves better picture quality with less SNR while offering compact size of MS. Abstract: In this treatise, we consider the image transmission by means of turbo coded Double Space-Time Transmit-Diversity (DSTTD) Code Division Multiple Access (CDMA) structured module using Polarization diversity (PD) through wireless networks. We consider Advanced Encryption Standard (AES) algorithm for data hiding and discrete wavelet transform (DWT) technique for image compression. We consider dual-Polarized antenna both at transmitter and mobile station (MS) to establish PD. At each MS, we implement non-linear detector which comprises of Block-nulling technique, which can separate two STBC block units and offers higher throughput. In specific, we examine the effects of nine tap delay pertaining to LTE-Extended vehicular channel models for DWT and encrypted image transmission of coded DSTTD-CDMA system. From our simulation, we observe that our system with PD provides secured image transmission with better picture quality for less SNR which offers high throughput with compact size of MS in the perspective of downlink DL communication. Graphical abstract: Coded DSTTD-CDMA system with Polarization diversity.